RhoA/ROCK-YAP/TAZ Axis Regulates the Fibrotic Activity in Dexamethasone-Treated Human Trabecular Meshwork Cells - Liu, Zhicheng; Li, Shanshan; Qian, Xiuqing; Li, Lin; Zhang, Haixia; Liu, Zhicheng (Frontiers in Molecular Biosciences, 2021)
High intraocular pressure (IOP) is a major risk factor for glaucoma, a leading cause of irreversible blindness. Abnormal fibrotic activity in the human trabecular meshwork (HTM) cells is considered to be partly responsible for the increased resistance of aqueous humor outflow and IOP. This study aimed to identify the fibrotic pathways using integrated bioinformatics and further elucidate their mechanism of regulating fibrotic activity in dexamethasone (DEX)-treated HTM cells. Microarray datasets from the GEO database were obtained and analyzed by GEO2R. Bioinformatics analyses, including GO and KEGG analyses, were performed to explore biological functions and signaling pathways of differentially expressed genes (DEGs). The fibrotic pathways and targets were determined by western blot, RT-qPCR, or immunofluorescence staining. The cellular elastic modulus was measured using an atomic force microscope. A total of 204 DEGs, partly enriched in fibrotic activity (collagen-containing ECM, fibroblast activation) and Rap1, Ras, TGF-β, and Hippo pathways, were identified. Experimental results showed that DEX induced fibrotic activity and regulated the expression of RhoA/ROCK in HTM cells. Similarly, the constitutively active RhoA (RhoAG14V) also promoted the fibrotic activity of HTM cells. Mechanistically, RhoAG14V induced the expression and nuclear translocation of YAP/TAZ to produce CTGF. Moreover, inhibition of ROCK or YAP decreased the expression of Collagen I and α-SMA proteins induced by DEX or RhoAG14V in HTM cells. In conclusion, these results indicate that RhoA/ROCK-YAP/TAZ axis plays a crucial role in regulating the fibrotic activity of DEX-treated HTM cells.